Substance use in rural trauma patients admitted for motor vehicle injuries before and during the COVID-19 pandemic - Toni Marie Rudisill; Lucie Steinmetz; James M. Bardes (BMC, 2023)
Abstract Background Urban trauma centers reported increased substance use among individuals injured in motor vehicle collisions (MVC) after the start of the COVID-19 pandemic. Little is known about individuals admitted to rural trauma centers during this time. This study's purpose was to describe substance use trends before and during the pandemic among individuals injured in MVC and treated at a rural Level-1 trauma center in West Virginia. Methods A cross-sectional analysis was performed using patients' medical records. The study population included individuals ≥ 18 years of age who received treatment for a motor vehicle-related injury between September 1, 2018, and September 30, 2021, and were tested for drugs and alcohol upon admittance. The pre-COVID-19 period was defined as September 1, 2018-March 15, 2020. The COVID-19 period was March 16, 2020-September 30, 2021. The primary dependent variable was the patients' drug test results. The primary independent variable was the time period. The data were analyzed using Chi-square tests, logistic regression, and proportional odds models. Results During this time, 1465 patients received treatment. On average, patients were 45 years ± 20 of age and male (57%). During COVID-19, 17% of patients tested positive for alcohol and 58% tested positive for non-alcohol drugs. After adjusting for patients' sex and age, the number of drugs that patients tested positive for was 31% higher during COVID-19 (aOR 1.31; 95% CI 1.08, 1.58). The proportion of patients testing positive for cannabinoids (p = 0.05), opioids (p = 0.001), and stimulants (p = 0.010) increased from pre-COVID-19 to COVID-19 periods. Conclusions Drug and alcohol use increased among trauma patients admitted to a rural trauma center during COVID-19. Significant increases were seen in the number of drugs and for cannabinoids, opioids, and stimulants.